2013
DOI: 10.1007/s10157-013-0857-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease induced dysfunction of high density lipoprotein

Abstract: Traditional risk factors do not account for increased cardiovascular disease in patients with chronic kidney disease (CKD), particularly individuals whose CKD has progressed to end-stage kidney disease requiring dialysis. CKD patients on dialysis show little to no cardiovascular benefits from lipid-lowering therapy and thus have an exaggerated residual cardiovascular risk. High density lipoprotein (HDL) quantity and functionality may explain some of the residual risk. CKD affects the composition and disrupts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…17,18 Other investigators have also found that HDL composition and function is significantly altered in patients with CKD and ESRD such that the HDL molecule could become paradoxically proinflammatory. 19,[22][23][24] In fact, a study in a cohort of Japanese MHD patients found that higher HDL-C concentrations were associated with higher levels of oxidized HDL, which were also associated with increased CV mortality. 17 Likewise, we have found that elevated serum HDL-C (.50 mg/dL) levels in prevalent MHD patients were associated with higher all-cause and CV mortality.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Other investigators have also found that HDL composition and function is significantly altered in patients with CKD and ESRD such that the HDL molecule could become paradoxically proinflammatory. 19,[22][23][24] In fact, a study in a cohort of Japanese MHD patients found that higher HDL-C concentrations were associated with higher levels of oxidized HDL, which were also associated with increased CV mortality. 17 Likewise, we have found that elevated serum HDL-C (.50 mg/dL) levels in prevalent MHD patients were associated with higher all-cause and CV mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Probably some of the residual risk in CKD patients is explained by changes in the level, composition, and functionality of HDL, which may contribute to the excess risk of CVD ( 187 ). Thus, therapy should be aimed at improving HDL function, possibly by targeting specific moieties within the HDL particle ( 188 ). In patients with CKD elevated levels of VLDL-C and apoB, and low levels of HDL-C and apoA-I, are associated with increased risk of ASCVD ( 189 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…Free cholesterol is then re-esterified by lecithin-cholesteryl acyltransferase (LCAT) and this conversion generates hydrophobic cholesterol esters that become embedded in the core of the lipid-poor discoid HDL particle, an action which can be described as "loading" of the HDL particle. This process results in the transformation of discoid lipid-poor HDL3 into (79,110). The impairment of the HDL antioxidant activity in ESRD patients is associated with significant reduction of the HDL-associated antioxidant enzymes, paraoxonase1 and glutathione peroxidase (107,111).…”
Section: Alterations In High Density Lipoprotein Metabolismmentioning
confidence: 99%